Analisis Perilaku Agresif pada Remaja di Depok Sleman Yogyakarta - Rista Islamarida; Mamik (Jurnal Kesehatan, 2022)
Adolescence is called a transitional period of development between childhood and adulthood, which involves biological, cognitive, and sociocosional changes. Emotional changes in adolescents can lead to aggressive behavior. Aggressive behavior is an outpouring of emotion as a reaction to individual failure that is exposed in the destruction of human beings or objects with elements of deliberation expressed by verbal words and nonverbal behavior. The aim of this research is to analize of aggressive behavior in adolescent. The methode of this research is is descriptive analitic. Total sample 140, with sampling total sampling technique. This research was conducted at SMK PI Ambarrukmo 1 Depok Sleman. The result of the research is obtained that the overwhelming majority of adolescent aggressive behavior has a low aggressive behavior, majority verbal aggressive behavior in medium category, and majority physical aggressive behavior in low category. sociocosional changes. Emotional changes in adolescents can lead to aggressive behavior. Aggressive behavior is an outpouring of emotion as a reaction to individual failure that is exposed in the destruction of human beings or objects with elements of deliberation expressed by verbal words and nonverbal behavior. The aim of this research is to analize of aggressive behavior in adolescent. The methode of this research is is descriptive analitic. Total sample 140, with sampling total sampling technique. This research was conducted at SMK PI Ambarrukmo 1 Depok Sleman. The result of the research is obtained that the overwhelming majority of adolescent aggressive behavior has a low aggressive behavior, majority verbal aggressive behavior in medium category, and majority physical aggressive behavior in low category.